Chloride-Less Approach Using Waste Linker Source in Zirconium-based Metal-Organic Framework (UiO-66) - Azmin A.N.; Misran H.; Matsumoto A. (World Scientific, 2024)
UiO-66 was synthesized using a chloride-less approach with waste plastic bottles as a possible organic linker at room temperature. UiO-66 features an arrangement of structure from the coordination of zirconium-based metal clusters interconnected by benzene dicarboxylate (BDC) linkers. BDC can be extracted from waste plastic bottles by depolymerization. The structural comparison of UiO-66 using a pristine linker and PET-derived BDC linker was investigated with and without the presence of chloride ions. The (011), (111), (002), and (022) reflection planes from X-ray diffraction peaks for all samples show successful UiO-66 crystal formation. Thermal analysis on as-synthesized samples exhibited the decomposition in three stages of weight loss which are attributable to the solvent's evaporation at ca. 170C, loss of water molecules physisorbed in the structure at ca. 371C, and mass reduction at ca. 540C due to decomposition of organic linkers, respectively. FT-IR spectra exhibited absorption peaks corresponding to the stretching vibration (?-H) in asymmetric and symmetric C-H bonds in aromatic compounds originating from BDC. By using the Scherrer equation, the primary crystallite size was calculated at a range of ca. 15-32nm. The crystallite size calculated showed a similar value to the grain observed using a Williamson-Hall (WH) plot in the range of ca. 14-29nm. However, the WH plot for samples without chloride ions showed small crystallite sizes as well as low relative crystallinity suggesting loose agglomerations of the particles. 2023 World Scientific Publishing Company.